Primary Prevention of Major Cardiovascular and Cerebrovascular Events with Statins in Diabetic Patients: A Meta-Analysis - de Vries, Folgerdiena M.; Denig, Petra; Pouwels, Koen B.; Postma, Maarten J.; Hak, Eelko (Drugs (New York, N.Y.), 2012)
Background Patients with diabetes mellitus are at increased risk of developing cardiovascular disease. Controlling lipid levels has a preventive effect on the occurrence of major cardiovascular and cerebrovascular events. Individual trials have shown varying data on the efficacy of treatment with lipid-lowering statin therapy in the primary prevention of such events in diabetes. Objective The objective of this study was to assess the efficacy of statins in the primary prevention of the first-time occurrence of a major cardiovascular or cerebrovascular event in diabetic patients. Secondary endpoints were fatal/non-fatal stroke, fatal/non-fatal myocardial infarction and all-cause mortality. Methods A systematic search for trial reports was conducted in PubMed, EMBASE, The Cochrane library and clinicaltrials.gov for the years 1966–2011. Reference lists of reviews and meta-analyses of related subjects were searched. High-quality, randomized, double-blinded clinical trials comparing a statin with placebo for the primary prevention of major cardiovascular and cerebrovascular events in diabetic patients were selected. Only large studies with a minimum of 500 diabetic participants followed-up for at least 2 years were included. Endpoints were major cardiovascular and cerebrovascular events. Trial and patient characteristics were extracted by three researchers. The quality of the included studies was tested with the Jadad score. The combined effect on primary as well as secondary endpoints was measured with a fixed-effect model. Publication bias was examined with a funnel plot. Results Four trials were included, for a total of 10 187 participants. Treatment with statins in the primary prevention of major cardiovascular and cerebrovascular events in diabetic patients resulted in a significant relative risk (RR) reduction in the first-time occurrence of major cardiovascular or cerebrovascular events (RR 0.75, 95% CI 0.67–0.85), fatal/non-fatal stroke (RR 0.69, 95% CI 0.51–0.92) and fatal/non-fatal myocardial infarction (RR 0.70, 95% CI 0.54–0.90) and a non-significant RR reduction in all-cause mortality (RR 0.84, 95% CI 0.65–1.09). Among the studies there was non-significant heterogeneity in the individual effect estimates and no publication bias. Limitations Exclusion criteria and endpoints varied slightly between studies. The type and dosing of statin therapy differed between studies. Non-compliance in the statin treatment group and the use of statin treatment in the placebo group could have led to lower risk reductions. Conclusion Treatment with statins in primary prevention among diabetic patients has a significant beneficial effect on event rates of the first-time occurrence of a major cardiovascular or cerebrovascular event, fatal/non-fatal stroke and fatal/non-fatal myocardial infarction. There was a non-significant RR reduction in all-cause mortality.